Trinidad Imperial College of Tropical Agriculture - Briant (Davidson and Todd Ltd., Trinidad, 2010)
Exterior view of the building housing the Imperial College of Tropical Agriculture. It is located in St. Augustine, Trinidad and was used to provide training in Tropical Agriculture for West Indian and British Commonwealth students.
Colour: Green, Blue, Red, Cream, Brown and Grey ; Style: Landscape ; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Imperial College of Tropical Agriculture; ICTA; Universities and colleges